El análisis financiero y la evaluación de los indicadores de la gestión, endeudamiento y liquidez - Campoverde Cortez, Yaritza Alejandra (2015)
The research called “FINANCIAL ANALYSIS AND EVALUATION OF INDICATORS OF MANAGEMENT, DEBT AND LIQUIDITY" allows to fulfill the objectives and referring to perform a financial analysis by applying financial ratios, with In order to determine the economic situation of the company. The methodology applied for its implementation involved the collection of information through scientific articles indexed journals, direct observation of processes within the company and an interview with the management of it in order to get to know the problems of the entity. He followed this were applied to financial indexes, which through its results allowed to establish the respective analysis, which was used to build the main conclusions were reached, showing major way the lack of liquidity which is the company.